Garlic (Allium sativum) Fresh Juice Induces Apoptosis in Human Oral Squamous Cell Carcinoma: The Involvement of Caspase-3, Bax and Bcl-2 - Farrokh Farhadi; Salar Jahanpour; Kameliya Hazem; Amirala Aghbali; Behzad Baradran; Seyyed Mahdi Vahid Pakdel (Tabriz University of Medical Sciences, 2015)
Background and aims. There is no report on the apoptotic impact of Allium sativum L.(Garlic) on the oral squamous cell carcinoma (KB); hence, this study was designed to survey the apoptotic effects of garlic fresh juice (GFJ) on the KB cells. Materials and methods. MTTassay (MicrocultureTetrazolium Assay) was carried out to evaluate the cytotoxicity of GFJ on KB cells. Furthermore, TUNEL(Terminal deoxynucleotidyltransferase-mediated dUTP nick end labeling)and DNA fragmentation tests were performed to determine if GFJ is able to induce apoptosis in KB cells. Also a standard kit was used to assess caspase-3 activity in KB cells. Also western blotting was employed to evaluate the effect of GFJ on Bax:Bcl-2 ratio. Results. Significant cytotoxic effects were observed for the minimum used concentration (1g/mL) as calculated to be 77.97±2.3% for 24 h and 818±3.1% for 36h of incubation (P < 0.001). Furthermore, TUNEL and DNA fragmentation tests corroborated the apoptosis inducing activity of GFJ. Consistently, after treating KB cells with GFJ(1μg/mL), caspase-3 activity and Bax:Bcl-2 ratio were raised by 7.3±0.6 and (P <0.001) folds, respectively. Conclusion. The results of this study advanced that GFJ induces apoptosis in the KB cells through increasing caspase-3 activity and Bax:Bcl2 ratio which could be attributed to its organo-sulfurcomponents.